Enhanced Performance of Asymmetrically Clipped DC-Biased Optical OFDM Systems Using Adjacent Symbol Detection - Wei-Wen Hu (IEEE Photonics Journal)
Compared to the direct current (DC) biased optical OFDM (DCO-OFDM) and asymmetrically clipped optical orthogonal frequency division multiplexing (ACO-OFDM) schemes, the asymmetrically clipped DC biased optical OFDM (ADO-OFDM) has demonstrated a better balance between optical power efficiency and spectrum efficiency. However, both the traditional ADO-OFDM and ADO-OFDM with iteration receiver suffer from an error floor issue when a lower DC bias is allocated to the DCO-OFDM branch. In this paper, we propose an enhanced receiving technique for ADO-OFDM that introduces an adjacent symbol detection (ASD) scheme in the DCO-OFDM branch of ADO-OFDM, named as ASD-based ADO-OFDM (ASD-ADO-OFDM). Simulation results indicate that the proposed ASD-ADO-OFDM provides a lower bit error rate performance at lower DC bias and fewer computational complexity compared with traditional ADO-OFDM with iteration receiver.